Shoulder and hip roll differences between breathing and non-breathing conditions in front crawl swimming - Psycharakis, S.; McCabe, C. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The effect of breathing on body roll has been the topic of only a few studies, with body roll calculated for the whole trunk based on the assumption that the trunk moves as a rigid segment in front crawl. However, Psycharakis and Sanders (2008) indicated that the shoulders roll significantly more than the hips and reported differences in the temporal characteristics of shoulder roll (SR) and hip roll (HR) during non-breathing cycles. The purpose of this study was to examine the influence of breathing on SR and HR during front crawl swimming. METHODS: Six competitive male swimmers swam two maximum 25m front crawl trials under different conditions: non-breathing (NBr) and breathing on the preferred side (Br). Six video cameras (50Hz) and three-dimensional analysis methods were used as described by Psycharakis et al. (2005) and Psycharakis and Sanders (2008). The total SR and HR were calculated as the sum of the roll to both sides. SR and HR were also calculated separately for the breathing side (SR-BS; HR-BS) and the non breathing side (SR-NBS; HR-NBS). Statistical analysis was done with paired samples t-tests and significance was accepted at p<0.05. RESULTS: Swimming velocity was not significantly different between trials (Br: 1.76±0.09m/s; NBr: 1.80±0.08m/s). Total SR was significantly higher in the Br (120.3±7.7°) than the NBr trial (107.4±6.9°). No significant differences were found in the total HR (Br: 44.1±5.9°; NBr: 41.8±6.7°). SR was significantly higher than HR in both trials. SR-BS increased significantly in the Br trial, but there were no significant differences between the Br and NBr trials in HR-BS, SRNBS and HR-NBS. No significant differences were found in the Br or the NBr trials between SR-BS and SR-NBS, and HR-BS and HRNBS. DISCUSSION: Swimmers increased SR when breathing by increasing mainly the roll of the shoulders towards the breathing side. HR and swimming velocity did not seem to be significantly affected by the breathing action. These preliminary data need to be xpanded to larger sample sizes to confirm and generalise the findings.